2011
DOI: 10.1002/j.1556-6978.2011.tb01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Supervisee Incompatibility and Its Influence on Triadic Supervision: An Examination of Doctoral Student Supervisors' Perspectives

Abstract: A qualitative study was conducted to explore supervisors' experiences of supervisee incompatibility in triadic supervision. In‐depth interviews were completed with 9 doctoral student supervisors in a counselor education program, and a whole‐text analysis generated 3 categories. Supervisee incompatibility took a wide variety of forms and negatively affected the content of supervision, including its progress and productivity. It also negatively influenced the process of supervision, including the feedback and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…While supervision is considered the signature pedagogy for counselorsin-training (Bernard & Goodyear, 2013;Hein, Lawson, & Rodriguez, 2011;Scott, Ingram, Vitanza, & Smith, 2000) and most practitioners eventually engage in supervision, formal supervision training is a very recent phenomenon. Until recently, few supervisors were formally trained for this influential and critical role (Peake et al, 2002) and it was suggested that many supervisors operate from a "seat of the pants" approach (Blocher, 1983), relying on their own experiences, good and bad, to guide them.…”
Section: Introductionmentioning
confidence: 99%
“…While supervision is considered the signature pedagogy for counselorsin-training (Bernard & Goodyear, 2013;Hein, Lawson, & Rodriguez, 2011;Scott, Ingram, Vitanza, & Smith, 2000) and most practitioners eventually engage in supervision, formal supervision training is a very recent phenomenon. Until recently, few supervisors were formally trained for this influential and critical role (Peake et al, 2002) and it was suggested that many supervisors operate from a "seat of the pants" approach (Blocher, 1983), relying on their own experiences, good and bad, to guide them.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have stressed the importance of matching supervisees in triadic supervision (Hein et al, 2011;Stinchfield et al, 2007), but the present findings make clear that supervisee incompatibility can manifest in a wide variety of ways that supervisors may not always be able to anticipate. Similarly, the participants expressed a wide variety of perspectives on the type of compatibility that is most critical to consider when matching supervisees.…”
Section: Discussionmentioning
confidence: 69%
“…The forms of supervisee incompatibility that emerge in any given triad are likely to vary, and the more of these that can be eliminated before supervision begins, the more effective that triadic supervision is likely to be. Helping supervisors to detect supervisee incompatibility early in the supervision process and to address it in effective ways should also be a key aspect of their training (see Hein et al, 2011), and this seems particularly important for doctoral-student supervisors. Such training could occur during the weekly group supervision discussed earlier, a clinical supervision course, or another context, and could consist of direct instruction from a faculty member or other clinician, feedback from a faculty member and other triadic supervisors about videotaped supervision meetings, discussion and problem-solving activities, or various role-play activities, for example.…”
Section: Implications For Clinical Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, clinical supervision is viewed as one of the most integral components of developing essential counseling skills among counselors-in-training (Hein, Lawson, & Rodriguez, 2011). Traditional models are consistently reviewed for efficiency and effectiveness.…”
Section: Postmodern Approaches To Supervisionmentioning
confidence: 99%